Exploration of BIM Automatic Quantity Take Off for Contractor on Bridge Structural Model - Vendie Abma; Tri Nugroho Sulistyantoro; Fitri Nugraheni (G-Tech: Jurnal Teknologi Terapan, 2026)
The implementation of Building Information Modelling (BIM) in Indonesia’s construction industry has grown steadily, but it mainly focuses on the planning stage. One important function of BIM, automated quantity take-off (QTO), has great potential benefits for contractors during the construction phase. However, its use often faces challenges due to poor model quality. This study explores the implementation of BIM-based automated QTO in a bridge construction project to support digital construction practices from a contractor’s viewpoint. A structured modeling approach that follows Level of Development (LOD) 350 was used to improve model quality, ensure data consistency, and allow reliable quantity extraction and shop drawing generation within the BIM environment. The QTO results for the concrete and reinforcement materials in this analysis showed a total concrete volume of 2,075.30 m³, and the reinforcement volume was 381,548.21 kg. The findings also highlight the need to align modeling practices with the requirements of the construction phase to fully take advantage of BIM. Overall, BIM-based automated QTO can enhance construction performance, reduce material waste, and improve contractor decision-making, providing evidence to support broader industry adoption and informing future guidelines and policy initiatives for digital construction in Indonesia.